Digital workflow for mini-implant-assisted rapid palatal expander fabrication-a case report - Li-Fang Hsu; Won Moon; Shih-Chin Chen; Kelvin Wen-Chung Chang (BMC, 2023)
Abstract Background Non-surgical mini-implant assisted rapid palatal expansion, or midfacial skeletal expansion, is a paradigm-shifting concept that in recent years has expanded the envelope of orthopedic movement in the transverse direction for adult patients. Although adding mini-screws to a rapid palatal expander is not complicated, accurate and successful expansion strongly depends on the device's position and its relation to the resisting structures of the maxillofacial complex. Case presentation This article presents a digital workflow to locate the optimal position of the Midfacial Skeletal Expander (MSE) device in a CBCT-combined intraoral scan file and describes how to transfer the MSE position intra-orally with properly sized bands during the device fabrication. The complete digital workflow of MSE fabrication and its application for a Class III orthognathic surgical case is presented in detail. Conclusions This report describes a completely digital process that can accurately position the MSE device according to the orientation and morphology of maxillary basal bone, which is crucial in adult cases demand maxillary expansion.